2012
DOI: 10.1371/journal.pone.0035686
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Intramolecular Communication in a Hyperthermophilic Acylaminoacyl Peptidase: A Molecular Dynamics Investigation

Abstract: Protein dynamics and the underlying networks of intramolecular interactions and communicating residues within the three-dimensional (3D) structure are known to influence protein function and stability, as well as to modulate conformational changes and allostery. Acylaminoacyl peptidase (AAP) subfamily of enzymes belongs to a unique class of serine proteases, the prolyl oligopeptidase (POP) family, which has not been thoroughly investigated yet. POPs have a characteristic multidomain three-dimensional architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 76 publications
(125 reference statements)
0
46
0
Order By: Relevance
“…Additionally, in the monomeric structure, the N-terminal helix α1 does not feature any highly populated paths of interactions to the rest of the protein. This is a marked difference with the hyperthermophilic ApAAP variant, in which the hydrophobic residues of helix α1 mediate long-range interactions to the N-terminal domain and the catalytic site [36]. Moreover, a larger number of salt-bridge networks characterize the ApAAP interface between the two domains [36].…”
Section: Hub Residues Involved In Intramolecular Interactions In Monomentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in the monomeric structure, the N-terminal helix α1 does not feature any highly populated paths of interactions to the rest of the protein. This is a marked difference with the hyperthermophilic ApAAP variant, in which the hydrophobic residues of helix α1 mediate long-range interactions to the N-terminal domain and the catalytic site [36]. Moreover, a larger number of salt-bridge networks characterize the ApAAP interface between the two domains [36].…”
Section: Hub Residues Involved In Intramolecular Interactions In Monomentioning
confidence: 99%
“…This is a marked difference with the hyperthermophilic ApAAP variant, in which the hydrophobic residues of helix α1 mediate long-range interactions to the N-terminal domain and the catalytic site [36]. Moreover, a larger number of salt-bridge networks characterize the ApAAP interface between the two domains [36]. The main hubs are characterized by a ΔΔG value greater than 0.5 kcal/mol upon alanine mutations (Fig.…”
Section: Hub Residues Involved In Intramolecular Interactions In Monomentioning
confidence: 99%
See 2 more Smart Citations
“…Using its CSU (contacts of structural units) server, we analyzed the interactions of the residues on the domain boundaries of apAPH and AFEST involved in, and then chose the residues with the least contacts as the recombination sites. Some researchers have shown that the interdomain interactions are crucial to the conformation and consequently stability and function of enzymes [8,28]. The propeller domain of apAPH and cap domain of AFEST are very different in sequence, size, and structure.…”
Section: Discussionmentioning
confidence: 99%